ANALISIS PELANGGARAN MAKSIM PADA FILM BERNAFAS DALAM LUMPUR - Widyasana, Boris Candra; Wijaya, Febri Pratomo Ramadhan (Translation and Linguistics (Transling), 2024)
This study aims to describe the maxims violation that occurs in the movie titled "Bernafas dalam Lumpur" which was released in 1991. This research is a qualitative descriptive study with a pragmatic approach that uses Grice's cooperative principle theory. The data source used is all the conversations that occur between the characters. The method used is the observation and note-taking method. The observation method is used to observe the maxim violations that occur in the utterances that appear in the film, and the note-taking method is used to record conversations that violate the maxims. The results of the study show that there are violations of maxims in the form of maxim of relevance, maxim of quality, maxim of quantity, and maxim of manner.